Advancements IN Eeg Technology: A New Frontier IN Real-Time Mental Health Monitoring AND Intervention (Journal of Pharmaceutical Negative Results, 2020)
Objective: This study evaluated the effectiveness of recent advancements in electroencephalography (EEG) technology for real-time mental health monitoring and intervention, specifically focusing on the impact of portable, AI-enhanced EEG devices in detecting and managing symptoms of anxiety and depression.Methods: The group consisted of 100 patients with generalized anxiety disorder or major depressive disorder who were randomly assigned to the experimental group (modern EEG monitoring with AI support) or control group (old-school EEG monitoring without real-time backing). Over 6 weeks, we measured each group’s mental health regarding symptom reduction, engagement, and detection accuracy. Changes in mental health were measured with the GAD-7 and PHQ-9 scales, and EEG data were analyzed for biomarkers.Results: Compared with the control group, the experimental group's symptoms were significantly reduced by 30%, which is an extremely strong sign that feedback in real-time is good. The cutting-edge EEG system detected 87% of mental health biomarkers, far greater than the 60% of standard EEG recording. Participants in the experimental group were more engaged and satisfied thanks to the live feedback received by AI-enabled EEG machines.Conclusion: The evidence confirms that high-throughput EEG technology with real-time functions is better at monitoring and intervening in mental health. These systems can be applied to clinical practice with AI-enhanced accuracy and real-time symptom treatment, which would likely revolutionize mental health care through proactive and personalized treatment approaches.